Anti-Realism Doesn't Dissolve by Realism: A Study of Epistemological Aspects, Methods of Constructing Modern Physics Knowledge on the Dualism of Light - Sohibun; Setiawan, Agus; Ahmad Samsudin (Undiksha, 2023)
This article aims to provide insight into epistemology for how to construct new knowledge based on the views of realism and anti-realism in one of the modern physical theories of dualism of light. This article presents views on the theory of dualism of light starting from the epistemology of light, light as a wave, light as a particle and light dualism. The method used in this study is a critical literature review, which is a type of critical review to analyze and evaluate many sources on the topic of modern physics, especially dualism of light and its epistemological philosophy to construct knowledge of dualism of light, a comparison of realism versus antirealism about the dualism of light. The result is that in constructing new knowledge, the view of anti-realism does not necessarily fall away and produces a new view of realism. It can be seen from the dualism of light, in constructing knowledge, the anti-realist view with its theory (classical physics) is not necessarily wrong and fails when there is a new theory from the view of realism (modern physics). even from this case, philosophically the theory that is formed from the views or facts of empirical results forms new facts and the theory applies the power of theory as a bridge.